"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Invisible work at work and the reproduction of gendered social service organizations - Lavee, Einat; Kaplan, Amit (Gender, Work and Organization, 2022)
Des études démontrent que la convergence du néolibéralisme et des impératifs de la nouvelle gestion publique crée des conditions dans lesquelles les prestataires de services sociaux entreprennent divers types de travail non rémunéré, réaffirmant le rôle du genre dans la prestation de services. En s’appuyant sur ces arguments, cette étude explore le processus par lequel les pratiques non rémunérées restructurent le genre dans les organisations de services sociaux, en utilisant le concept de « travail invisible ». En appliquant la méthode d’enquête de l’ethnographie institutionnelle, nous examinons les expériences des travailleurs des services sociaux dans le secteur public israélien et opérationnalisons le travail non rémunéré comme des ressources personnelles informelles que les travailleurs fournissent aux clients. L’analyse de 185 entretiens approfondis a révélé trois principaux cadres discursifs que les travailleurs utilisent pour justifier la fourniture de ressources personnelles. Grâce à ces cadres, les pratiques informelles deviennent invisibles en tant que travail à plusieurs niveaux – pour soi-même, pour l’organisation et pour la société. Tout comme le travail invisible dans le ménage, son invisibilité sur le lieu de travail constitue une force principale dans la reproduction des organisations de services sociaux sexuées.
Keywords: approches et analyses; asie; discipline; inégalités; israël; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible; travail social; éthnographie institutionnelle

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Paid and unpaid work during the Covid-19 pandemic: A study of the gendered division of domestic responsibilities during lockdown - Borah Hazarika, Obja; Das, Sarmistha (Journal of Gender Studies, 2021)
The Covid-19 pandemic and the strategies implemented to deal with it have had economic and societal repercussions all over the world. In India, a nationwide lockdown was initiated on 25 March 2020 which continued in a diluted form as we were conducting the interviews for the paper in July 2020. The lockdown brought activities outside the home to a standstill and people were expected to stay indoors in order to ensure social distancing and break the chain of infection. The lockdown sparked its own problems and triggered discussions on issues including economic hardship and domestic violence. The question of how domestic responsibilities are shared among adults in families has also come to the forefront of debate. As hired part-time help was discontinued under lockdown, parents who had hitherto outsourced childcare and housework were suddenly left to fend for themselves. This article attempts to explore the manner in which such unpaid domestic responsibilities, especially childcare, were shared between parents in middle-class homes. The gendered nature of this division of housework and care work, and its varied implications on the paid work and careers of mothers and fathers, is the focus of inquiry. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; conciliation famille-travail; confinement; covid-19; discipline; division sexuelle du travail; famille; inde; pandémie; projet charge mentale; périodes historiques; régions géographiques; science politique; science politique et droit; soins aux enfants; thématiques; travail; travail domestique

The physical burden of water carrying and women’s psychosocial well-being: Evidence from rural nepal - Tomberge, Vica Marie J.; Bischof, Janine Stefanie; Meierhofer, Regula; Shrestha, Akina; Inauen, Jennifer (International Journal of Environmental Research and Public Health, 2021)
Dans les pays à faible revenu, de nombreuses femmes transportent de lourdes charges d'eau potable pour leur famille sur des terrains difficiles. Cela peut nuire à leur santé et à leur bien-être. La présente étude est la première à examiner la charge physique du transport de l'eau et le bien-être psychosocial des femmes, ainsi que la manière dont cette relation est modérée par les conditions environnementales et sanitaires. Des enquêteurs locaux formés ont mené des entretiens avec 1 001 femmes dans cinq communautés rurales du Népal. En outre, des mesures objectives ont été utilisées pour évaluer le poids porté et la distance par rapport à la source d'eau. La charge physique du transport de l'eau a été calculée à partir du poids, de la distance et de la fréquence des déplacements. Son association avec le bien-être psychosocial a été modélisée à l'aide d'équations d'estimation généralisées. Deux autres modèles incluaient le terrain et le prolapsus utérin comme modérateurs. La charge physique du transport de l'eau est directement liée à une détresse émotionnelle plus élevée et à une réduction du fonctionnement quotidien. Cette corrélation était exacerbée pour les femmes transportant sur un terrain vallonné par rapport à un terrain plat, et pour celles qui souffraient d'un prolapsus utérin. Nos résultats soulignent l'importance d'un accès adéquat à l'eau pour le bien-être psychosocial des femmes, en particulier pour les populations vulnérables telles que les femmes en mauvaise santé (par exemple, prolapsus utérin) ou celles vivant dans des terrains vallonnés. Les résultats soulignent en outre l'interdépendance de l'Objectif de développement durable (ODD) 6 : accès à l'eau, de l'ODD 3 : santé et bien-être et de l'ODD 5 : égalité des sexes.
Keywords: 2000 à aujourd'hui; asie; bien-être psychosocial; environnement; histoire et politique; népal; projet charge mentale; périodes historiques; régions géographiques; santé; santé des femmes*; thématiques; transport de l'eau potable; travail; travail reproductif

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

Voix et travail des femmes dans les développements touristiques à Hampi - Biddle Bocan, Charlotte (Université du Québec à Montréal, 2020)
Cette recherche partira des points de vue des femmes qui travaillent dans les infrastructures touristiques de Hampi pour comprendre les développements touristiques dans cette région. À la lumière des propos énoncés par les personnes participantes à une recherche terrain, nous analyserons les enjeux politiques et sociaux provoqués par ces développements touristiques. Cette recherche a donc trois objectifs (1) mettre de l’avant les points de vue de celles, ceux qui ne sont pas entendues dans un discours dominant sur les développements touristiques (2) de comprendre ces développements touristiques à partir du point de vue de celles, ceux qui les vivent au quotidien, qui travaillent au sein de ces infrastructures touristiques et, partant de leurs voix (3) démontrer les implications sociales et politiques des restructurations suscitées par ces développements touristiques en remettant en question la littérature néolibérale et hégémonique sur les développements touristiques. Cette recherche répond à la question suivante : comment les développements touristiques à Hampi sont expliqués, organisés et revendiqués par les populations de basses castes et classes qui travaillent dans les infrastructures touristiques du village ? Nous verrons que les femmes considèrent le tourisme comme une opportunité afin de mieux répondre à leurs besoins et à ceux de leur communauté, toutefois l’importance grandissante que prendra le tourisme dans le village entrainera l’implication d’acteurs urbains et supranationaux qui déstabilisent l’organisation du travail des femmes et de leurs communautés entrainant tranquillement leur exclusion du village. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : tourisme, néolibéralisme, travail des femmes, capitalisme, développement, Inde
Keywords: IREF; asie; discipline; inde; mémoires/thèses; néolibéralisme; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques; tourisme; travail; travail des femmes*

The missing doctors — An analysis of educated women and female domesticity in Pakistan - Mohsin, Mariam; Syed, Jawad (Gender, Work and Organization, 2020)
While the percentage of female students in medical schools in Pakistan is as high as 80–85 per cent, the percentage of female doctors in the medical workforce remains below 50 per cent. Our findings draw on in-depth interviews with 31 female doctors to show that the reasons behind the gap between female medical students and female medical professionals are multifold and multilayered, ranging from individual reasons to organizational and sociocultural reasons. We use an adapted version of the relational framework developed by Syed and Özbilgin in 2009 to offer a contextual and multilevel understanding of female domesticity in Pakistan. The study suggests that the problem of female doctors dropping out of the medical workforce is a reflection of the interplay of social, organizational and individual factors, which are tied together by social norms. Practical implications suggest that making hospitals and health organizations more inclusive of women and their needs could be a starting point for policymakers to address the gender gap in the medical profession. © 2020 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; asie; conciliation famille-travail; famille; femmes* médecins; maternité; pakistan; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

Its about time we care about an equitable world: Women's unpaid care work and COVID-19 - Sarrasanti Ardinugroho, Nediana; Donkor, Felix Kwabena; Santos, Claudia; Tsagkari, Marula; Wannous, Chadia (IEEE Engineering Management Review, 2020)
Unpaid care work, mostly performed by women, is a central but undervalued contributor to economies. During the COVID-19 pandemic, the need for unpaid care work increased due to restricted movement, social isolation, and economic challenges. This pandemic has highlighted the urgency of recognizing and valuing women's work at the household level which has been systematically overlooked. At the same time, it has increased the demand for technology usage, exposing the gender digital divide. This article aims to shed light on the additional burden women are facing, especially when trying to balance unpaid care work with paid employment from the seclusion of their homes. We do this by reviewing a number of surveys conducted in Indonesia. We combine this with other examples from additional contexts in order to draw attention to a global trend of amplified inequalities and struggles women are experiencing. We advocate for an urgent paradigm shift by providing vital recommendations for policymakers and managers.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; covid-19; indonésie; pandémie; pauvreté; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail non rémunéré; travail précaire; violences; violences domestiques; violences envers les femmes*

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Benefits and constraints of the agricultural land acquisition for urbanization for household gender equality in affected rural communes: A case study in Huong Thuy Town, Thua Thien Hue Province, Vietnam - Thi, Nhung Pham; Kappas, Martin; Wyss, Daniel (Land, 2020)
Le gouvernement vietnamien a mis en œuvre l'acquisition de terres agricoles pour l'urbanisation (ALAFU) depuis 2010, ce qui a provoqué un niveau élevé de transition socio-économique dans le pays. Dans cet article, nous avons appliqué l'approche genre et développement pour découvrir comment l'ALAFU a influencé l'égalité des sexes au sein des ménages dans les zones touchées de la province de Thua Thien Hue, au Vietnam. Les données de cet article ont été principalement collectées à partir de deux enquêtes auprès de groupes de ménages, de quatre discussions de groupe et de six entretiens avec des informateurs clés. Le groupe 1 couvre 50 ménages affectés dont les terres agricoles ont été acquises pour l'urbanisation, tandis que le groupe 2 se compose de 50 ménages dont les terres agricoles n'ont pas été confisquées. Les résultats révèlent que l'ALAFU a conduit à un accès réduit aux terres agricoles pour le groupe 1, mais a contribué à une augmentation du statut économique des femmes des deux groupes en créant des opportunités d'emploi non agricoles avec un bon revenu. Cependant, la plupart de leurs nouveaux emplois sont encore informels, comportent des risques potentiels et la charge de travail de soins non rémunérés est lourde. De plus, bien que le taux de participation des femmes à la prise de décision au sein du ménage ait augmenté, la qualité de la participation est limitée. Leur participation aux activités sociales et aux cours de formation professionnelle s’est améliorée de manière insignifiante. Par conséquent, si le Gouvernement continue de promouvoir l’ALAFU, il devra prendre en compte les inégalités structurelles entre les sexes pour atteindre ses objectifs de développement durable.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; care; participation citoyenne des femmes; projet charge mentale; périodes historiques; régions géographiques; terres agricoles; thématiques; travail; travail du care; urbanisation; vietnam

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

Work-family balance and the subjective well-being of rural women in Sichuan, China - Yue Shui; Xu, Dingde; Liu, Yi; Liu, Shaoquan (BMC Women's Health, 2020)
Background Due to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.Methods This study used a sample survey of 380 rural women in rural areas of Sichuan Province to measure rural women’s cognition of work-family, coordination and handling of conflicts, post-conflict choices, and subjective well-being; the study constructs an ordered multi-class logistic regression model to explore the impact of work-family conflict on the subjective well-being of rural women in rural regions.Results The study result shows that: (1) The level of subjective well-being of rural women is generally high, and 70% of women feel satisfied or very satisfied. (2) The factor which impacts the subjective well-being among rural women most is work-interfering-with-family conflict, followed by work-family balance and confidence in conflict coordination.Conclusion This study can enhance our understanding of rural women in rural areas, and provide a reference for formulating policies to improve people’s life satisfaction.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; bien-être psychosocial; chine; conciliation famille-travail; famille; femmes rurales; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail